Pockets of poverty in the northern states of Malaysia - Saidatulakmal Mohd,; Nur Azirah Zahida Mohamad Azhar,; Nurul Syifaa Mohd Shakil,; Abdelhak Senadjki,; Mohammad Darabi Golshani Iran, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Despite Malaysia’s tremendous economic growth and remarkable achievement in poverty reduction for the nation, pockets of poverty remain in certain regions. Pockets of poverty could be analysed using micro data when macro data is unable to provide a clear understanding on the existence of poverty. This study assesses the pockets of poverty in the Northern States of Malaysia. Northern States of Malaysia consist of Perlis, Kedah, Penang and Perak. The objectives of this paper are twofold: to identify pockets of poverty in the Northern States of Malaysia using household income data and to determine the factors that affect these pockets of poverty. Pockets of poverty in this region are investigated among strata, ethnic groups, income level and education. For this purpose, the National Poverty Line Income (PLI) is determined to specify the poor. Logistic probability function is estimated to assess factors that influenced poverty in the Northern States of Malaysia. This study uses the Household Income Survey (HIS) data for 2009 and 2012. From data analysis, it could be concluded that pockets of poverty exist among elderly, women, Bumiputera and those living in the rural areas. Logistic probability analysis indicates that variables that are statistically significant in influencing poverty are age, gender, location, education level, Chinese (ethnic group) and married (marital status). These findings are vital to develop appropriate policy orientation in targeting the correct group in solving poverty.